Synthesis and characterization of Alendronate functionalized Poly (l-lactide) polymers for engineering bone tumor targeting nanoparticles - Sriadibhatla, Soma Sekhar (Kansas State University, 2016)
Nanomedicine-based therapeutics have exhibited clear benefits when compared to unmodified drugs, which include improved pharmacokinetics, drug retention, targeting efficiency, and minimizes toxicity. Every year thousands of bone cancer cases are diagnosed in the United States. Moreover, development of bone metastasis occurs in over 80% to 90% of various cancers that metastasize and signals the entry of the disease into an incurable phase. Cancer in bones can cause pain, fractures, hypercalcemia, and compression of the spinal cord, due to deposits that can erode into the bone using bone-absorbing cells. Bisphosphonates are drugs that reduce the activity of bone-absorbing cells and targets overexpressed calcium. They are characterized pharmacologically to inhibit bone resorption, skeletal distribution, and renal elimination. In addition, they can target bone microenvironment and bind strongly with calcium. The goal of this thesis is to engineer targeted nanomedicine drug with the ability to spatiotemporally control therapeutics delivery to the bone. Herein we synthesized biopolymers with functional end group moieties as alendronate (a molecular member of bisphosphate), which can target overexpressed calcium ions at the vicinity of the bone lesion where bone resorption takes place. In order to achieve our goal, a ring opening polymerization of cyclic L-lactide initiated by ALE in the presence of catalytic amount of stannous octoate was conducted in an inert environment. Thus, formed polymers are characterized for their chemistry and physicochemical properties using various analytical tools. These polymers were characterized by nuclear magnetic resonance (¹H-NMR) and Fourier Transfer Infrared Spectrometer (FT-IR), which shows monomer conversion and the presence of amide and phosphate moiety. Thereafter we engineered bone-homing polymeric nanoparticles of 80nm diameter by nanoprecipitation for controlled delivery of Dox, a first line anticancer drug used in clinics. The in-vitro results show that the nanoparticles have the ability to accumulate and internalized into the bone cancer cells, deliver drugs efficiently, and are least toxic. Therefore, innovative and efficient bisphosphonate functionalized Poly-l-lactide polymers were synthesized to target bone microenvironment.
Keywords: Nanomedicine; Bone tumor; Drug delivery; Targeting; BisphosphonatesPoly(l-lactide)